Road traffic accidents attending casualty in a tertiary care hospital : a 03 year study from South Western India - Chourasia, Sachin; Radhakrishna, K. V.; Rautji, Ravi; K., Shivakumar D. (International Journal of Research in Medical Sciences, 2019)
Background: Road Traffic Accident (RTA) is any vehicular accident occurring on the roadway i.e. originating on, terminating on, or involving a vehicle partially on the roadway. Road traffic accidents are a human tragedy which has an immeasurable impact on the families affected. The WHO estimates that over 1.2 million people pass away every year on the world’s roads, and between 20 and 50 million fall victims to non-fatal injuries. The incidence of RTA remains poorly measured in India. Methods: The present study is conducted at casualty department of a tertiary care hospital in South Western India among victims of road traffic accident. This cross sectional study was conducted to elucidate the role of various factors involved in road traffic accidents and to study demographic profile and injury pattern among RTA victims. All the reported RTA cases from 1st January 2016 to 31st December 2018 were included in the study. Results: A total of 875 cases of RTA were studied. There were 83.77%(n=733) male and 16.23%(n=142) female accident victims. Most of the patients were aged between 21 and 30 years. Monsoons witnessed 46.63%(n=408) cases. Most cases occurred between 6 and 12pm (54.4%, n=476). Commonest injury was a simple injury (72.91%, n=638), dangerous injuries (27.09% percent, n=237) and dead was (7.43%, n=65). The highest number of accidents took place in the month of June (19.09%, n=167) and on Sundays (22.17%). Among the motorized vehicles, two-wheeler drivers were more (76.91%, n=673) involved in accidents. In this study 17.60% (n=154) were under influence of alcohol while driving. Conclusions: This study shows there are multiple factors associated with road traffic accidents. Most of the factors responsible for RTA and its fatal consequences are preventable. India, as a signatory to the Brasilia declaration, intends to reduce road accidents and traffic fatalities by 50% by 2022. A comprehensive multipronged approach can mitigate most of them.